PENTINGNYA BIMBINGAN KELOMPOK DALAM PERKEMBANGAN PRIBADI DI PANTI ASUHAN MITRA PAYAKUMBUH - Najla Hana Rifasya; Hidayani Syam; Nutria Desi (CV. ADIBA AISHA AMIRA, 2024)
Group coaching is an important approach in helping individuals overcome various challenges and develop their potential. This article discusses the importance of group tutoring in the context of personal, social, and academic development. By focusing on key aspects such as social support, personal growth, and improving interpersonal skills, group coaching can provide significant benefits to its participants. Group tutoring allows individuals to share experiences, create supportive relationships, and learn from each other. This helps reduce feelings of isolation and improves participants' emotional well-being. In addition, group tutoring also provides a platform for self-exploration, where participants can explore their values, beliefs and life goals. In an academic context, group tutoring can increase learning motivation and facilitate cooperative learning. Group discussions and exchange of ideas can enrich participants' understanding of the subject matter. In addition, group tutoring can help in overcoming learning difficulties and improving study skills.